Beyond Balancing: China's approach towards the Belt and Road Initiative. Issue 112 (4th July 2018) - Zhou, Weifeng; Esteban, Mario
Abstract: This article explores the motivations and calculations behind China's Belt and Road Initiative. It argues that China's efforts to enhance regional multilateral cooperation across the Eurasian space through the BRI are strongly motivated by a multifaceted grand strategy. First, China makes use of the BRI as a vehicle of soft balancing to frustrate the US containment and encirclement of China, and undermine its dominance in Eurasia and beyond. Second, China intends to promote alternative ideas and norms and build its role as a normative power through the BRI for fostering the legitimacy of its rising power. Third, China seeks to form a bargaining coalition through the BRI and AIIB to reshape global governance and transform the existing international system in a way that reflects its values, interests and status. Overall, the BRI serves as a decisive strategic maneuver for China to ensure security and promote power status in the international order, moving from a rule-taker to rule-maker.